Functions and Patterns of Code-Switching in Social Media: A Study on Audreyfannyau’s Instagram Captions. - Jofita, Keneswangi; Sigit Haryanto (LPPM Universitas Advent Indonesia, 2026)
This study explores the patterns and functions of code-switching in Instagram captions by Audrey Fanny Aulia, an Indonesian beauty influencer. As social media increasingly reflects the everyday language practices of bilingual users, code-switching has become a key strategy in digital communication. Using a qualitative descriptive approach, this research analyzes 30 captions posted between September 2024 and June 2025. The analysis applied Poplack’s typology of code-switching—intra-sentential, inter-sentential, and tag-switching and the communicative function framework of Appel and Muysken, which includes expressive, referential, directive, phatic, and metalinguistic functions. The findings reveal that inter-sentential code-switching appears most frequently, followed by intra-sentential and tag-switching. Regarding functions, the expressive and referential functions were found to be the most common, indicating that the influencer often switches languages to express emotions and connect more closely with her audience. These results suggest that code-switching on social media serves not only as a linguistic feature but also as a communicative strategy to enhance engagement and personal expression. The study highlights how bilingual influencers like Audrey use language performatively to construct and negotiate identity in digital spaces. It contributes to a broader understanding of multilingual discourse in informal online contexts and offers insight into language use in today’s influencer culture.